TINGKAT KECEMASAN ATLET KARATE DOJO GARUDA SUMBAWA PADA PERTANDINGAN KOSN TINGKAT PROVINSI TAHUN 2020 - Rezi Auliani; Susi Yundarwati; Elya Wibawa Syarifoeddin (Universitas Pendidikan Mandalika, 2021)
The problem that arises is that the Dojo Garuda Sumbawa karate athletes when participating in the 2020 KOSN championship did not achieve any achievements, even though the athletes who participated in the KOSN were athletes who had achievements at the national level. Based on this, the researchers tried to find out whether the level of anxiety when participating in the KOSN championship greatly affected, because this type of championship using video recordings was the first time it was held. The purpose of this study was to determine the level of anxiety of the Karate athlete Dojo Garuda Sumbawa at the provincial level KOSN competition in 2020. This research is a type of qualitative descriptive research. The population in this study was the Dojo Garuda Sumbawa karate athlete in 2020, totaling 60 people. Sampling in this study was carried out by purposive sampling, with certain considerations or criteria, namely the Karate Dojo Garuda Sumbawa athlete who had won a match at the national level and who met the criteria amounted to 25 people. The data analysis technique used in this research is descriptive analysis using percentages. The results showed that the results of the anxiety level of the Dojo Garuda Sumbawa karate athlete at the 2020 Provincial KOSN Competition in the